Impact of Incision Placement on Ischemic Complications in Microsurgical Breast Reconstruction. Issue 2 (February 2022) - Tevlin, Ruth; Griffin, Michelle; Karin, Mardi; Wapnir, Irene; Momeni, Arash
Abstract : Background: Nipple-sparing mastectomy is associated with greater patient satisfaction than non–nipple-sparing approaches. Although various nipple-sparing mastectomy incisions have been described, the authors hypothesized that incision location would impact the rate and location of ischemic complications to the mastectomy skin flap. Methods: A prospectively maintained database was queried to identify patients who underwent nipple-sparing mastectomy with immediate microsurgical reconstruction with a minimum postoperative follow-up of 12 months. The impact of incision location on postoperative ischemic complications was investigated. Major complications were defined as those that required reexploration in the operating room or inpatient management; minor complications were amenable to outpatient management. Multivariable logistic and linear regression were performed to investigate risk factors for postoperative complications following breast reconstruction. Results: Eighty-seven patients met inclusion criteria. The following nipple-sparing mastectomy incisions were used: radial with a periareolar extension (39 percent), inframammary fold (31 percent), vertical with a periareolar extension (22 percent), vertical (6 percent), and radial (2 percent). Seven patients (8 percent) had major complications, whereas twenty-six patients (29.9 percent) developed minor postoperative complications. Inframammary fold incisions were associated with significantly greater rates of mastectomy skin flap necrosis ( p = 0.002), whereas periareolar incisions were associated with significantly greater rates of postoperative nipple-areola complex necrosis ( p = 0.04). Conclusions: The authors report a significant association between incision location and ischemic complications to the breast skin envelope in microsurgical breast reconstruction. The authors observed a significant association of inframammary fold and periareolar incisions with mastectomy skin flap and nipple-areola complex necrosis, respectively. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.